Penggunaan Media Visual Kartu untuk Meningkatkan Penguasaan Kosa Kata Bahasa Arab Siswa Kelas X Agama Madrasah Aliyah Negeri 1 Gresik - Choirul Jamroni (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
This research was motivated by the problem of learners still having difficulty in memorizing Arabic vocabulary. Learners are crowded themselves, the concentration of learning is less and the lack of use of interesting learning media, especially in Arabic vocabulary materials, which results in the ability to memorize the vocabulary of learners is low. To address the problem, the researcher is interested in using the mufrodat card media. The formulation of the problem in this study is "Is the use of mufrodat card media able to improve the ability to memorize arabic vocabulary of students of class X Religion MAN 1 Gresik?". This class action research aims to "Knowing the use of mufrodat card media in improving the ability to memorize Arabic vocabulary in students of class X Religion MAN 1 Gresik. This research is a class action research (PTK). The subjects of this study were class X Agama learners who numbered 33 learners. This study was conducted in two cycles. Based on the results obtained during the implementation of class action research, it can be explained that: the results of improving the ability to memorize learners after applying the mufrodat card media. In the pre-cycle completed learners amounted to 9 (34.62%) and the incomplete 17 (65.38%). In cycle I experienced an increase in completed learners amounting to 14 (53.85%) and the incomplete amounted to 12 (46.15%). In cycle II there was an increase from 26 completed learners 20 (76.92%) who were not completed 6 people (23.08%). Based on the results of research and data analysis it can be concluded that the use of mufrodat card media can improve the ability to memorize the Arabic vocabulary of students of class X Religion MAN 1 Gresik.